Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Kecamatan Beji Kota Depok - I Gusti Komang Fajar Nugraha; Eigis Yani Pramularso; Hardani Hardani (Universitas Kristen Indonesia Toraja, 2024)
The function of human resources is very important. In achieving organizational goals, it is seen as an important driving force. Only with the hard work of the organization's human resources can the company's goals be realized. This study aims to determine whether the variables of workload, work environment partially affect employee performance and to determine whether workload and work environment simultaneously affect employee performance at the Beji District Office, Depok City. This research method uses a quantitative method. The sampling technique in this study used a saturated sampling technique of 58 people. This study uses primary data and data collection techniques using questionnaires which will then be analyzed using validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, linearity tests, multiple linear regression tests, t tests, f tests, determination coefficient tests. The results of this study indicate that workload partially affects employee performance positively and significantly, while the work environment partially does not affect employee performance positively and significantly. So it can be concluded that workload and work environment simultaneously affect employee performance positively and significantly